Metformin therapy and cognitive dysfunction in patients with type 2 diabetes: A meta-analysis and systematic review. Issue 10 (March 2020) - Zhang, Qing-Qing; Li, Wen-Shan; Liu, Zhou; Zhang, Hui-Li; Ba, Ying-Gui; Zhang, Rui-Xia
Abstract: Background: Type 2 diabetes (T2D) is a risk factor for cognitive dysfunction. The relationship between metformin therapy and cognitive function in patients with T2D is unknown. Therefore, we determined the relationship between metformin therapy and cognitive function in patients with T2D using a meta-analysis. Methods: We systematically searched the Cochrane library, PubMed, and Embase to identify studies showing correlations, and we calculated hazard ratios (HRs). Results: We identified 10 studies including 254, 679 participants. Metformin significantly reduced the occurrence of cognitive dysfunction in patients with T2D (HR 0.90; 95% CI [0.88, 0.92]). Compared with other hypoglycemic drugs, sulfonylureas also improved cognitive dysfunction (HR 0.92; 95% CI [0.88, 0.95]). Thiazolidinediones gave no statistically significant improvement in cognitive dysfunction (HR 0.97; 95% CI [0.87, 1.07]). The use of insulin aggravated cognitive dysfunction (HR 1.34; 95% CI [1.24, 1.43]). In the subgroup analysis of various regions controlling for age, gender, education, diabetes course, complications, metformin administration and dosage, and follow-up time, metformin significantly improved cognitive dysfunction in patients in the Americas and Europe (HR 0.69; 95% CI [0.63, 0.74]), (HR 0.71; 95% CI [0.66, 0.76], respectively), while metformin did not significantly improve cognitive dysfunction in Asian patients (HR 0.99; 95% CI [0.96, 1.01]). Conclusions: Metformin significantly improved cognitive dysfunction in patients with T2D. Sulfonylureas also improved cognitive dysfunction. Thiazolidinediones had no significant effect on cognitive dysfunction. The use of insulin aggravated cognitive dysfunction. Metformin improved cognitive dysfunction more significantly in patients in the Americas and Europe than in Asia.